Analysis of buccal gingival thickness in maxillary implants and its relation to gingival biotype (Research, Society and Development, 2022)
Objectives: This study aimed to evaluate vestibular gingival thickness in unitary implants located in the anterior maxilla through a cone beam tomography. Material and methods: After visual classification of the gingival biotype of the 32 patients selected for this study (16 patients with thin biotype and 16 patients with thick biotype) measurements of the vestibular tissue thickness were made at 2, 4 and 6 mm from the gingival margin in the apical direction in the most longitudinal transverse cut of the implant and the contralateral tooth through tomographic cone beam examination for soft tissue. The data of age and gender of the patients, mean buccal wall thickness of the implants and contralateral natural teeth, and the use of connective tissue graft (CTG) were tabulated for descriptive analysis. Results: For thin gingival biotype, mean vestibular gingival thickness varied between 1.26 ± 0.31 mm (teeth) and 2.65 ± 0.93 mm (implant), and for thick biotype varied from 1.77 ± 0.58 mm (teeth) and 3.01 ± 0.96 mm (implant). The use of CTG increased the buccal thickness of thick biotype when compared to thin biotype without CTG. Conclusions: It was not possible to establish a direct relationship between the classification of the gingival biotype of the contralateral teeth and the gingival biotype of the implants installed in the anterior region of the maxilla, but CTG was shown to be efficient in increasing gingival tissue thickness.